Performance Analysis of Doubly Fed Induction Generator Using Vector Control Technique - Aye Myat Thin; Nang Saw Yuzana Kyaing (Institute of Advanced Engineering and Science, 2015)
There are many solar power and wind stations installed in the power system for environmental and economic reasons. In fact, wind energy is inexpensive and the safetest among all sources of renewable energy, it has been recognized that variable speed wind turbine based on the doubly fed induction generator. It is the most effective with less cost and high power yield. This paper has chosen doubly fed induction generator for a comprehensive study of modelling, performance and analysing. DFIG wind turbine has to operate below and above synchronous speed which requires smooth transition mode change for reliable operation to be controlled to provide stability for the power system. Hence its performance depends on the generator itself and the converter operation and control system. This paper presents completed mathematical model of DFIG with its AC/DC/AC converter driven by DC machine. The rotor is considered fed by a voltage source converter whereas the stator is connected to the grid directly. The capacity of the wind power generation is 1.5MW. The voltage rating and frequency for this system are 575V, 50Hz .This paper show detailed model of DFIG.